Konsep Rahn (Gadai) Dalam Islam Dan Peraturan Perundang-Undangan Indonesia Kajian Fikih Muamalah - Alexander, Ongky; Fauzi, Muhamad; Yani, Ahmad; Siswoyo, Siswoyo (Hutanasyah : Jurnal Hukum Tata Negara, 2023)
In muamalah, Islam also recognizes pawn activities or what is called rahn. Which rahn conrtract is an agreement on a debt between rahin (pawner/ borrower) and murtahin (pledgee/lender), that is, one who pawns hisgood as collateral for his debt. To fulfill economic needs, sometimes humans have many difficulties, various ways can be done so that their needs can still be fulfilled. For example by pawning valuables such as gold land and so on. Various views of Islamic leaders in discussing rahn. In general, pawning activities are permitted with specified conditions and pillars. Islamic pawnshop activities (rahn) with standard rules still have many problems, such as legal norms from rahn. So it is also necessary to discuss the norm in rahn activities which expected to be in accordance whith Islamic shari’a. In terms of collateral (rahin) it is a legal issue that also needs to be discussed in the concept of pawning. There is a shift in the paradigm of pawn in the terminology of Islamic law and economics to become debt. Furthermore, this paper aims to explain the conceptof rahn, law and other matters relating to rahn (pawn) so that people know more about pawning and the concept of pawning that is justified aaccording to Islam.